Drug Metabolism and Pharmacokinetics of Dammarane Triterpenoids - Zhang, Sainan; Zhao, Yuqing (Current Drug Metabolism, 2016)
Dammarane triterpenoids are widely distributed in plants and are implicated in various bioactivities and pharmacological effects. This review focuses on advancements in dammarane triterpenoid metabolism, particularly drug design and development, including radiolabeling, absorption, distribution, metabolism, excretion, and pharmacokinetics, which can accurately describe the behaviors of dammarane triterpenoids. This review contributes to the systematic and consistent research and development of dammarane triterpenoids. Their structures and activities, radiolabel application, absorption, distribution, and pharmacokinetic characteristics, possible degradation pathways, metabolic enzyme induction or inhibitory effect, and structure-activity relationships have been described. New intranasal and intra-tympanic administration routes and microdialysis technology have also been introduced. These techniques not only improve the limits of dammarane triterpenoids on absorption and distribution but also facilitate the design and study of these compounds as potential drugs.
Keywords: distribution